Pengaruh Profitabilitas, Ukuran Perusahaan, dan Komite Audit Terhadap Audit Report Lag - Syahzuni, Barlia Annis; Wulandari , Christine (Juara: Jurnal Riset Akuntansi, 2024)
This research is intended to explore the implications of independent variables, which include profitability, company size, and audit committee on audit report lag as the dependent variable. The focus of this research is on business entities operating in the property and real estate services sector listed on the Indonesia Stock Exchange during 2020-2022. The research population includes 68 companies, with a total sample that meets the research criteria of 204. The variable measurements in this study involve Return on Equity (ROE) to measure profitability, Ln total assets to measure company size, and the number of audit committee members who have an accounting background to measuring the performance of the audit committee. Analysis is carried out using statistical applications. This research conducted a comparative causal analysis using the multiple liner analysis method by carrying out the classical assumption test, F test, T test, and coefficient of determination test (R2). The test resulted in the finding that there was a negative correlation between profitability and audit report lag, while company size did not show any influence on audit report lag. On the other hand, the audit committee shows a positive influence on audit report lag.